2005
DOI: 10.1080/02699050500109944
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of activity and virtual reality based balance exercise programmes for adults with traumatic brain injury: Perceptions of participants and their caregivers

Abstract: Both exercise programmes offered benefits in addition to improved balance. The VR participants had greater improvements on quantitative measures and provided more comments expressing enjoyment and improved confidence. Applications in terms of community reintegration and quality of life are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
110
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(124 citation statements)
references
References 40 publications
(42 reference statements)
8
110
0
6
Order By: Relevance
“…[38] While this study did not find a significant difference between groups, it did demonstrate that both groups improved their balance, and that participants receiving the VR-based treatments enjoyed their therapy experience more than those in the standard care group. [38,39] While these data do not clearly demonstrate that the VR-based therapy was advantageous to standard care, they do suggest that VR-based interventions may be effective in treating patients with TBI who are receiving rehabilitation for balance deficits.…”
mentioning
confidence: 68%
See 3 more Smart Citations
“…[38] While this study did not find a significant difference between groups, it did demonstrate that both groups improved their balance, and that participants receiving the VR-based treatments enjoyed their therapy experience more than those in the standard care group. [38,39] While these data do not clearly demonstrate that the VR-based therapy was advantageous to standard care, they do suggest that VR-based interventions may be effective in treating patients with TBI who are receiving rehabilitation for balance deficits.…”
mentioning
confidence: 68%
“…[111] In regards to balance, VR has been investigated as a tool to assess deficits post injury in athletes with mild TBI, [112][113][114] and as a therapeutic technique to treat long-term balance deficits in patients more than six months post TBI. [39] It should be noted that while the latter study failed to show statistically significant group differences, it did show that persons receiving VR-based treatment did improve their balance as much as a group receiving standard PT. [39] Acceptance or enjoyment of the use of VR has been assessed across several of these studies, all of which have reported positive feedback from participants.…”
Section: Emerging Techniques For Balance Treatments: Virtual Realitymentioning
confidence: 88%
See 2 more Smart Citations
“…Furthermore, there is now a growing evidence base to support their use in a variety of different rehabilitation applications including mobility and aerobic fitness [13][14][15], post-stroke rehabilitation of hand-arm function [16][17][18], balance [14,[19][20][21], pain distraction while undergoing treatment/therapy [22], and treatment of amblyopia ("lazy eye") [23].…”
Section: Introductionmentioning
confidence: 99%